(untitled) (Seminário Internacional de Informação, Tecnologia e Inovação, 2024)
The history and memory of Amerindian peoples are marked by processes of colonization, subalternization and silencing, above all, because it is marked by orality. However, critical movements to overcome these conditions emerge, which have decolonial thinking at their base. It aims to analyze the transformations of the Pan-Amerindian myth of the “bird nester” from the perspective of the ideas of dissemination of information, culture and memory, taking as a reference a bibliographical research based on a narrative literature review. Procedurally, the historical and social aspects surrounding colonialism and coloniality are discussed, which reflect on the perception of the subject, reaching the critical perspective of decoloniality in Information Science. Furthermore, it addresses the purpose of myths and their effectiveness. It is concluded that what appears to be “noise” in the information can be understood and explained as “music”, and, therefore, capable of helping in the search for the original understanding of this information, which, many times, is already endowed with multiple and diverse meanings.